2010
DOI: 10.1089/jwh.2009.1465
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Cancer Initially Presenting as Intramammary Metastases and Mimicking a Primary Breast Carcinoma: A Case Report and Literature Review

Abstract: Surgeons should be aware that ovarian cancer may rarely metastasize to intramammary and axillary nodes, mimicking a primary breast carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Other authors have reported the role of 18 F-FDG PET/CT in the diagnosis of inguinal lymph node metastases from ovarian carcinoma [8,9]. To our knowledge, this is the first report describing the value of 18 F-FDG PET/CT in detecting rectal lymph node metastasis and in treatment planning for recurrent ovarian carcinoma.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Other authors have reported the role of 18 F-FDG PET/CT in the diagnosis of inguinal lymph node metastases from ovarian carcinoma [8,9]. To our knowledge, this is the first report describing the value of 18 F-FDG PET/CT in detecting rectal lymph node metastasis and in treatment planning for recurrent ovarian carcinoma.…”
Section: Discussionmentioning
confidence: 77%
“…Ovarian cancer cells frequently spread to regional lymph nodes such as the iliac and para-aortic nodes [3]. Uncommonly, these cells may also spread to the rectal [4-7], inguinal [8], and intramammary [9] lymph nodes. However, few reports have described how to detect and treat such metastases [10].…”
Section: Introductionmentioning
confidence: 99%
“…This was also surgically resected. The patient was alive without evidence of disease 20 months later .…”
Section: Introductionmentioning
confidence: 93%
“…The earliest report of ovarian cancer metastasis to an IMN involved a 30‐year‐old woman with a stage I mucinous tumor (see Table ) . Since that report in 2000, eight articles have been published involving 23 additional women . Demographic, medical, and treatment characteristics of these women are summarized in Table to aid in comparing those cases to the one reported herein.…”
Section: Case Reports and Case Series Of Ovarian Cancer Metastases Tomentioning
confidence: 99%